Absence of menstruation in female athletes: why they do not seek help - Saskia J. Verhoef (BMC, 2021)
Abstract Background It is known that amenorrhea is highly prevalent among female athletes. However, a large percentage of them do not seek help if this complaint occurs. We performed this study to gain more insight into the reasons why female athletes do not seek help when experiencing amenorrhea and how care for these women could be improved. Method Qualitative focus group research. Female athletes were approached to take part in a focus group. They were asked about the main reasons for not reporting amenorrhea and how care for amenorrhea, in their opinion, would ideally be organised. The women were asked to make a list of their top five reasons for both subjects and discuss this among their peers. Results According to the participants, the five main reasons for not reporting the amenorrhea were: (1) normalizing of the subject, (2) the absence of menstruation is not perceived as a problem by the athletes themselves, (3) experienced shame and taboo, (4) prioritisation of sports performance, and (5) denial. Factors to improve care around menstrual cycle problems in female athletes were: (1) informing athletes, coaches, trainers and mentors, (2) informing doctors, (3) conducting more research on long-term consequences, (4) breaking the taboo on menstrual problems, and (5) having a multidisciplinary collaboration between different specialisms. Conclusion By informing athletes, coaches, trainers, and mentors about menstrual cycle problems in athletes, more awareness among those groups can be created. According to the athletes, more research is needed on the long-term consequences of amenorrhea in sports, to enable them to make a better assessment of their possible future health risks. Women experience a taboo on discussing menstrual problems; role models discussing the problem may help in decreasing the taboo. A multidisciplinary collaboration of health care providers may improve care around female athletes with menstrual problems.